Effect of different chemicals on infective potential of teliospores of Neovossia indica - SINGH, SUKHWANT; SINGH, P P; BEDI, P S (The Indian Journal of Agricultural Sciences, 2013)
The effect of different chemicals On infective potential of tliospores of Neovossia indica (Mitra) Mundkur was evaluated during 1988 by computing their overall effect on the sporidial potential index of the germinated Leliospores. The sporidial potential index was based on the gemination (%) of teliospores, germinated spores (%) having sporidiogenous promycelium and the number of sporidia borne on each such promycelium. Among the various vitamins and growth-regulators, only riboflavin (100 ppm), folic acid (50 ppm), indoleacetic acid (50 ppm) and gibberellic acid (100 ppm) were effective in increasing the infective Potential of the teliospores. All the organic acids and phenolic compounds only inhihited the fernimationÂ but also adversely affected sporidia formation.